Multiple uremic tumoral calcinosis in periarticular soft tissues with chronic renal failure: a case report - He, Lijin; Li, Meifang; Lin, Chenlan; Yan, Kunlong; Yang, Chengmin; Tang, Jing (Frontiers in Endocrinology, 2023)
Uremic tumoral calcinosis (UTC) is an uncommon and severe complication of hemodialysis therapy. The most important pathogenic factor involved in UTC is an increase in calciumphosphorus products. We report here a patient undergoing hemodialysis for renal failure caused by hypertensive nephropathy who presented multiple UTCs in the right shoulder, left elbow and wrist. After surgical excision, they all recurred, with a similar UTC in the left shoulder. By observing the imaging features of various imaging examinations during the whole period of this case, including X-ray, computed tomography (CT), magnetic resonance imaging (MRI), and single-photon emission computed tomography (SPECT), we highlight the importance of imaging for evaluating the state of UTC regarding treatment options, further deepening our understanding of the imaging manifestations for this disease and their clinical significance.